2022
DOI: 10.1038/s41467-022-32946-1
|View full text |Cite
|
Sign up to set email alerts
|

NETosis and thrombosis in vaccine-induced immune thrombotic thrombocytopenia

Abstract: Vaccine-induced immune thrombotic thrombocytopenia (VITT) is a rare yet serious adverse effect of the adenoviral vector vaccines ChAdOx1 nCoV-19 (AstraZeneca) and Ad26.COV2.S (Janssen) against COVID-19. The mechanisms involved in clot formation and thrombocytopenia in VITT are yet to be fully determined. Here we show neutrophils undergoing NETosis and confirm expression markers of NETs in VITT patients. VITT antibodies directly stimulate neutrophils to release NETs and induce thrombus formation containing abun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(91 citation statements)
references
References 41 publications
4
64
0
Order By: Relevance
“…This is in line with the in vitro binding data between PF4 and ChAdOx1 reported by Baker et al 34 . The anti-PF4 IgG will then lead to the downstream activation cascade as it has been shown that IgG from TTS patients is capable of activating platelets and neutrophils and inducing thrombosis in a murine model (hFcγRIIa/hPF4) 35 .…”
Section: Understanding the Biological Mechanisms And Impact Of Vaccin...mentioning
confidence: 99%
“…This is in line with the in vitro binding data between PF4 and ChAdOx1 reported by Baker et al 34 . The anti-PF4 IgG will then lead to the downstream activation cascade as it has been shown that IgG from TTS patients is capable of activating platelets and neutrophils and inducing thrombosis in a murine model (hFcγRIIa/hPF4) 35 .…”
Section: Understanding the Biological Mechanisms And Impact Of Vaccin...mentioning
confidence: 99%
“…After clonal expansion and isotype switching of one or a few B-cell clones, high titer IgG anti-PF4 antibodies are released into the circulation 57,58 . Immune complexes containing PF4 and anti-PF4 IgG cluster and signal through FcR IIA 47,79 , which generates procoagulant platelets, induces platelet/neutrophil aggregates 80 , and stimulates NETosis by neutrophils 47,56,79 . DNA released by NETosis amplifies immune injury and activates complement, which deposits on the endothelium 81,82 .…”
Section: Conclusion Unknowns and Future Directionsmentioning
confidence: 99%
“…Thus, heparin enhancement is not a feature of the platelet function assays used in VITT as it is in HIT. The newly formed immunoglobulin G (IgG) anti-PF4 antibodies in VITT can activate platelets [ 1 , 5 , 6 ] and neutrophils through FcγRIIa engagement leading to platelet activation and the release of neutrophil extracellular traps (NETs) [ 7 ]. While exposure to adenoviral vector vaccines is the precipitating cause of VITT, the precise stimulus for the development of the pathogenic anti-PF4 antibodies in the first place is unclear.…”
Section: Pathogenesismentioning
confidence: 99%
“…In recent translational studies, the thrombi in CVST associated with VITT were found to be rich in neutrophils, and markers of NETosis were found to be increased in VITT patients’ sera [ 1 , 46 ]. In a functional assay and in mouse models, blocking FcγRIIa receptors or inhibiting NETosis resulted in the abolishment of thrombus formation [ 7 ]. Thus, NETosis could be an important mechanism of VITT-associated CVST [ 47 ] and the brain endothelium may be more prone to thrombosis in VITT because of reduced levels of DNAse I expression [ 48 ].…”
Section: Clinical Presentationmentioning
confidence: 99%